O discurso jurídico e o sujeito interpretante: possíveis interpretativos e limites da interpretação - Aurélio Agostinho Verdade Vieito (2016)
The interpretation limits within the judiciary domain and its interpretative possibilities arethe main theme of current thesis. There is a need for the establishment of minimalstandards in the interpretation and comprehension processes between subjects, texts anddiscourse. The problem lies in the fact that in dialogue and monologue discourses thecommunicating subject attributes, through the enunciation, a determined place to theaddressee who is conceived and idealized within discourse. The role of the interpretingempirical subject is positing oneself at the place attributed to him in the discourse. Orrather, the interpreting interlocutor depends on himself alone (CHARAUDEAU, 2008, p.77). However, all individuals insert themselves within a community of speakers andsubjects, with a situated, historical and dialogical interpretative perspective. The paradoxprovides us food for thought on the limits of interpretation and possible interpretations.There is a need to delimit and map the interpretation sites within the juridical domain. Ahistorical summary on the interpretation of law was undertaken through a chronologicalapproach between current ideas of interpretation and the possible interpretations proposedby Charaudeau. The concepts of topoi, doxa, ethos and pathos are adopted to analyze acorpus composed of two decisions provided by the Labor Regional Court of the state ofMinas Gerais, Brazil, and by the Labor High Court in a public suit by the Labor CourtAttorney against CEMIG prohibiting outsourcing practiced by the state company.Charaudeau´s analytic devices were associated to Plantin´s argumentative model,Gadamer´s experience hermeneutics and Ricoeur´s hermeneutic circle. The interpretingsubject is focused within the communication condition, according to Charaudeau. Anargument is developed that a narrative construction, a configuration of facts and areconfiguration of the interpreting subject exist in juridical arguments. Results reveal thatjuridical decisions are interpretation sites or laws of passage in argumentation.